インテルサット カイセン ドウニュウ ニ トモナウ ショウワキチ ジシン モニタリング カンソク システム ノ コウシン - 金尾, 政紀; カナオ, マサキ; 土井, 浩一郎; ドイ, コウイチロウ; 坂中, 伸也; サカナカ, シンヤ; 上村, 剛史; ウエムラ, タケシ; 澤柿, 教伸; サワガキ, タカノブ; 千田, 克志; チダ, カツシ; et al. (2006)
P(論文) 南極・昭和基地では,2004年2月よりインテルサット衛星回線を利用した通信システムが立ち不がり,基地外との情報交換・通信能力が格段に向不した.昭和基地の地震モニタリング観測で収録される波形データは,これまでもインマルサット衛星回線によりUnix-to-Unix-Copy(UUCP)伝送を行ってきたが,収録サーバーを更新(geotail; IP:133.57.32.60)し,インテルサット回線を用いた伝送方式に変更した.短周期地震計(HES)と広帯域地震計(STS-1)の20 Hz連続サンプリングデータが,定期的に国内(国立極地研究所サーバー)へ自動伝送される.また常時IP接続により国立極地研究所から直接に,昭和基地の収録装置(geotail, 及びAD変換機Q680; IP:133.57.32.67)への遠隔ログインと各種コマンド操作が可能になり,国内から観測機器への制御が格段に容易になった.さらに,ネットワークカメラサーバーによるリモート監視を行うことで,データ収録状況の常時モニタリングが可能になり,現地での見回りの労力が半減した. 本稿では,インテルサット衛星回線の導入に伴う昭和基地の地震モニタリング観測・データ伝送システムの具体的な向不点について紹介する.また,将来のリモートデータ収録を視野に入れた,インテルサット回線を利用した遠隔データ収録試験について報告する.さらに,伝送データのアーカイブ方法と公開内容についても紹介する. The seismic observation system at Syowa Station, Antarctica, was partially improved in association with introduction of the INTERSAT communication link from February 2004. The workstation used for acquisition of the seismic signals was replaced by a new one (geotail; IP:133.57.32.60) at the Earth Science Laboratory (ESL). Digital waveform data have been automatically transmitted from a 24-bit A/D converter (Q680; IP:133.57.32.67) to the workstation on TCP/IP protocol by using `Comserv' software. Among several kinds of seismic signals, 20 Hz continuous data of both short-period (HES) and broadband (STS-1) seismometers have been automatically transferred once a day to the National Institute of Polar Research (NIPR) by using the Unix-to-Unix-Copy (UUCP) protocol via the INTERSAT link. Besides remote operations and monitoring data from NIPR to the acquisition system at ESL, Internet access to the observation system at Syowa Station has significantly improved. For instance, network cameras were introduced both in ESL and the Seismological Hut, which provide real-time images for monitoring related instruments, analogue recorders and room temperature measurements, even when nobody can approach the ESL or Hut during severe weather. The above improvements involving the INTERSAT link have brought several advantages not only to the data transport/communication processes but also to reduce daily ...